Molecular Identification and Sequence Analysis of Tobacco Leaf Curl Begomovirus from Jember, East Java, Indonesia - SRI HENDRASTUTI HIDAYAT; ORAWAN CHATCHAWANKAN PANICH; NOOR AIDAWATI (HAYATI Journal of Biosciences, 2008)
Begomovirus had been proved as the causal agent of leaf curl disease in tobacco in Indonesia, or commonly in Indonesia called as penyakit krupuk tembakau. Association of Begomovirus with the disease was further confirmed by sequence analysis. Amplification of the virus was conducted following whitefly (Bemisia tabaci Genn.) transmission. Fragment of DNA 1.6 kb was amplified by polymerase chain reaction (PCR) located within the replication initiator protein gene and coat protein gene (top region). Conserved sequence of stem loop region was found, included nonanucleotide sequence TAATATTAC present in all geminiviruses. Begomovirus associated with leaf curl disease in tobacco showed the closest relationship with Ageratum yellow vein virus - Zimbabwe, a strain of Tobacco leaf curl virus from Southern Africa. It was also known that Begomovirus associated with leaf curl disease in tobacco from Jember, East Java was different from other Indonesian Begomoviruses reported earlier. Key words: Begomovirus, leaf curl disease